Wrapping Tape Operation during Correction of Aortic Stenosis (15 Years of Clinical Experience) - V. V. Popov; O. O. Bolshak; S. P. Spysarenko; T. A. Malysheva (Ukrainian Journal of Cardiovascular Surgery, 2020)
The aim. To study the clinical possibilities of the original technique of the wrapping tape operation (WTO) of the dilated post-stenotic ascending aorta (AA) during surgical correction of aortic stenosis (AS).Materials and methods. The study group included 196 patients who were operated on for the prevailing AS combined with poststenotic dilation of the ascending aorta (PDAA) for the period from 01.01.2006 until 01.01.2020 at the National Amosov Institute of cardiovascular surgery of the National Academy of Medical Sciences of Ukraine. All the patients underwent aortic valve replacement (AVR) combined with the original technique of WTO. During echocardiographic examination, the diameter of the AA before surgery was 47.7±1.7 mm, and the diameter of the Valsalva sinuses was 37.4±1.8 mm. The original technique of the correction of PDAA included plication of the non-coronary Valsalva sinus, as the most vulnerable zone, reduction of the AA diameter, creation of its reliable framework in order to prevent further AA dilation in the long term.Results. Hospital mortality was 0.5%. In the long term, the outcomes in 185 patients (94.4% of the number of discharged patients) were studied. The follow-up period was 8.1±0.8 years. In the long-term period, 8 (4.1%) patients died. The AA diameter at the time of discharge was 39.1±1.5 mm and 40.3±1.1 mm in the long term, and the diameter of the Valsalva sinuses was 34.5±1.5 mm and 34.8±1.3 mm, respectively. Complications or deaths associated with the technique of the intervention on the aortic root and AA were not observed both at the hospital stage and in the long term. None of the patients was reoperated due to further AA dilation.Conclusions. The proposed technique has established itself as a fairly reliable, safe procedure. In addition, it is costeffective since it does not require the use of a vascular prosthesis. The technique is useful for the correction of AS and PDAA from 4.0 to 5.2 cm.